Asymmetric Petasis reaction for the synthesis of chiral α- and β-butadienyl amines. Issue 19 (3rd February 2021) - Xie, Yi-Wen; Zhao, Zhen-Ni; Lin, Zi-Wei; Wang, Yu-Hao; Liu, Ya-Qun; Huang, Yi-Yong
Abstract : Chiral α- and β-butadienyl amines are both available via the asymmetric Petasis reaction of pinacol homoallenyl- and isoprenylboronates. Abstract : The Petasis reaction using (1 S, 2 R )-1-amino-2-indanol as the substrate and an activator to construct α- and β-butadienyl amines in optically pure forms was realized, which are otherwise difficult to prepare. The reactions feature a metal-free nature, broad substrate scope, complete regioselectivities (γ-selectivity of pinacol homoallenyl- and isoprenylboronates), and high to excellent chirality induction (up to >20 : 1 dr). The favored nucleophilic addition across the Si-face of the imine intermediate was explained using DFT calculations of the six-membered chair-like transition state.